2009
DOI: 10.1111/j.1445-2197.2009.05111.x
|View full text |Cite
|
Sign up to set email alerts
|

Minilaparotomy abdominal aortic aneurysm repair in the era of minimally invasive vascular surgery: preliminary results

Abstract: The MIAS technique, for repair of infrarenal aortic aneurysms, is a safe and feasible procedure that combines the early advantages of endovascular repair with the long-term advantages of the traditional open repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In our study, 23% of the patients in Group B underwent minilaparotomy while in Group A no minilaparotomy was used. A previous case-control study conducted by Bakoyiannis et al 24 comparing OR for AAA with and without minilaparotomy showed significant better outcomes for minilaparotomy in terms of faster recovery and shorter hospital length of stay (4.0 ± 0.8 vs 9.7 ± 2.7, P < .05).…”
Section: Discussionmentioning
confidence: 86%
“…In our study, 23% of the patients in Group B underwent minilaparotomy while in Group A no minilaparotomy was used. A previous case-control study conducted by Bakoyiannis et al 24 comparing OR for AAA with and without minilaparotomy showed significant better outcomes for minilaparotomy in terms of faster recovery and shorter hospital length of stay (4.0 ± 0.8 vs 9.7 ± 2.7, P < .05).…”
Section: Discussionmentioning
confidence: 86%